Hacking artificial intelligence a leader's guide from deepfakes to breaking deep learning - Gibian, Davey, 1988- (Rowman & Littlefield, 2022)
"The ability to hack AI and the technology industry's lack of effort to secure it is thought by experts to be the biggest unaddressed technology issue of our time. This book sheds light on the many hacking risks, encouraging readers to address problems before they become catastrophic"--